PENDIDIKAN PRANATAL DALAM PESEPEKTIF ISLAM - Fathullah, Amal (UIN Antasari Banjarmasin, 2020)
ABSTRACTPrenatal education in an Islamic perspective is an interesting study from Islamic education experts because at this time in choosing a mate, children are more entitled to determine their mate compared to their parents. This is very far from the tradition exemplified by the Prophet and his companions. When someone wants to get married, almost no premarital education is carried out. Though this is very important to know because it involves the terms and pillars of marriage. In fact, the most important thing is that education carried out during pregnancy is no less important given the awareness of the positive or negative influence of education in an Islamic perspective, when parents are pregnant with their baby. Therefore, parents are required to maintain emotional stability and even Islam forbids dropping divorce when the wife is pregnant. This implies that the importance of prenatal education in the perspective of Islamic education and Islamic education experts should dissect this problem seriously.KEYWORDS: Prenatal Education; Divorce; Islamic Education.ABSTRAKPendidikan pranatal dalam perspektif Islam menjadi kajian yang menarik dari pakar pendidikan Islam karena saat ini dalam memilih jodoh anak lebih berhak dalam menentukan jodohnya dibandingkan dengan orangtuanya. Hal ini sangat jauh dari tradisi yang dicontohkan oleh Rasulullah dan para sahabatnya. Pada saat seseorang ingin menikah, hampir tidak ada lagi pendidikan pranikah yang dilakukan. Padahal hal ini sangat penting diketahui karena menyangkut syarat, dan rukun nikah. Bahkan yang terpenting adalah pendidikan yang dilakukan ketika hamil juga tidak kalah pentingnya dilakukan mengingat kesadaran akan adanya pengaruh positif ataupun negatif pendidikan dalam perspektif Islam justru sudah ada ketika orang tua sedang mengandung bayinya. Karenanya dituntut orang tuanya menjaga kestabilan emosi bahkan Islam mengharamkan menjatuhkan talak ketika Istri hamil. Hal ini mengsiyaratkan bahwa pentingnya pendidikan pranatal ini dalam perspektif pendidikan Islam dan para pakar pendidikan Islam semestinya membedah permasalahan ini secara serius.KATA KUNCI: Pendidikan Pranatal; Talak; Pendidikan Islam.